Rancang Bangun Panel Auto Transfer Switch (ATS) Pada Sistem Hybrid PLN – Panel Surya Berbasis Timer Switch - M. Ashar Tahir; Muhammad Irsan B (Universitas Islam Raden Rahmat, Malang, 2024)
Design of an Auto Transfer Switch (ATS) Panel on a Hybrid PLN Sistem – Timer Switch Based Solar Panel. Along with the times, modern technological equipment that is present today is very helpful for human life. Using the MCB, timer, contactor, panel box. The results of the study obtained electric current data from PLN when using a lamp load of 5, 10, 15, 20, 25 watts respectively, namely 0.03, 0.06, 0.09, 0.12, 0.15 A with a calculated voltage of 166 Volts. The current from the solar panel when using a light load of 5, 10, 15, 20, 25 watts respectively is 0.03, 0.06, 0.09, 0.13, 0.16 A with a calculated voltage of 166, 153 and 156 Volts. The lag time for moving from PLN to solar panels is 1.60 seconds. Savings using this hybrid sistem is 19,468 rupiah.